1998
DOI: 10.2307/3433830
|View full text |Cite
|
Sign up to set email alerts
|

An IARC Evaluation of Polychlorinated Dibenzo-p-Dioxins and Polychlorinated Dibenzofurans as Risk Factors in Human Carcinogenesis

Abstract: The International Agency for Research on Cancer (IARC) Monographs program reevaluated polychlorinated dibenzo-p-dioxins and evaluated polychlorinated dibenzofurans as possible carcinogenic hazards to humans in February 1997, using the most recent epidemiologic data on exposed human populations, experimental carcinogenicity bioassays in laboratory animals, and supporting evidence on relevant mechanisms of carcinogenesis. 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) was evaluated as carcinogenic to humans (IARC gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…The evidence from these three occupational cohorts thus indicates nothing at all about the human carcinogenicity of non-TCDD congeners, and this evaluation is entirely consistent with the International Agency for Research on Cancer's 1997 assessment of the evidence regarding these substances (McGregor et al 1998):…”
Section: Selection Of a Dose Metricsupporting
confidence: 58%
See 1 more Smart Citation
“…The evidence from these three occupational cohorts thus indicates nothing at all about the human carcinogenicity of non-TCDD congeners, and this evaluation is entirely consistent with the International Agency for Research on Cancer's 1997 assessment of the evidence regarding these substances (McGregor et al 1998):…”
Section: Selection Of a Dose Metricsupporting
confidence: 58%
“…We also conclude that Crump et al's extrapolation (Crump et al 2003) from Steenland et al's TCDD analyses (Steenland et al 1999(Steenland et al , 2001) to one based on TEQ is unjustified and overreaching because neither the epidemiologic data nor their meta-analysis of it support the inference that TEQ exposures close to background are likely to be carcinogenic to humans (Flesch-Janys et al 1998;McGregor et al 1998). Their extrapolation from TCDD to TEQ is especially troubling because it raises unnecessary concerns about the safety of our food supply.…”
Section: Resultsmentioning
confidence: 92%
“…DDT has been found to be estrogenic [1], TBT is believed to cause androgenic effects [5], and TCDD affects a wide range of complicated biological processes and is thought to be nongenotoxic [44]. Accordingly, microarray analysis of exposure of Tetrahymena to the toxicants suggested that the functions of the differentially expressed genes varied among toxicant-treated sets.…”
Section: Identification Of Differentially Expressed Genes and Categormentioning
confidence: 99%
“…They have been long known as being carcinogenic to laboratory animals, causing a wide range of tumors (66)(67)(68)(69), and are now confirmed as being carcinogenic to humans (7,(67)(68)(69)(70)(71)(72). TCDD causes cancer in multiple species, multiple strains, both sexes, and in multiple organs and tissues (66)(67)(68)(69). TCDD causes cancer by multiple routes, various durations of exposure, and ranges of exposure concentrations (66).…”
Section: 378-tetrachlorodibenzo-pdioxin (Tcdd)mentioning
confidence: 99%